(3WHbGJ abgGA Gdjef hQDSGA GdRefs - (3YeQ Hf Ydj Hf SeQI Hf GdMSjf GdLYOj,J (B586 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CdgefG dMeOg CeG HYO aEfi CSCd Gddg JYGdi GdYjhf Ydi JdNjU eG CQOJg ef PcQ GjGe abgGA Gdjef , heHdZ CYeGQge s
(3BNQgG (B:s
(3hefge Gdabjg YHO dGdg GdUMGZi eScfg GdUMGY Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B22 - (3U(B69s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hbO CJe GdeDda JCdjaI SfI (B576(3g` s
(3cJHJ CSeGA GdeJQLejf Ydi GdgGeS HGdMeQI s
(3YdjgG HYV GdJbjjOGJ s
(3hHgG dUa ai HYV GdehGVY s
Keywords: (3GdJGQjNs